The Eastern Boar / Lion Coinage - Wünsch, Julian (KOINON: The International Journal of Classical Numismatic Studies, 2025)
Due to recent finds, the corpus of diobols of eastern provenance depicting the forepart of a wild boar on the obverse and the head of a roaring lion on the reverse has increased significantly. This anepigraphic silver coinage was inspired by prototypes from Kyzikos. First attributed to Lykia, its connection to the Athenian imitations and the Sophytos coins, both probably struck in Parthia, was eventually recognized. The following contribution presents the first die study of the eastern boar/ lion series. It is based on close to 90 specimens, representative examples of which are illustrated on Plates 1-4. Exploring its possible placement within the early coinage of Parthia, it is suggested that this series was issued as a small change supplement to the imitative Athenian coins.